국내에서 재배된 밀 유전자원의 통밀에서 단백질 및 아라비노자일란 함량 분석 - 양진우; Jinwoo Yang; 박진희; Jinhee Park; 손재한; Jae-han Son; 김경훈; Kyeong-hoon Kim; 김경민; Kyeong-min Kim; 정한용; Han-yong Jeong; et al. (Korean journal of crop science, 2021)
Recently, phytochemicals in whole grains have received increasing attention because the increased consumption of whole grains and whole grain products has been associated with a reduced risk of chronic diseases. Among the phytochemicals in whole wheat, arabinoxylan influences various physiological activities and can aid the treatment of numerous health conditions, either directly or indirectly. In this study, 614 wheat germplasms, collected from the world, were cultivated in 2018 and harvested in 2019 in South Korea. The qualities of these whole grains, including seed protein content, were evaluated using the NIR spectrophotometric method, and arabinoxylan content was determined using enzymatic methods. The ash content was 0.36 to 2.80% and protein content was 7.66 to 20. The SDS-sedimentation for gluten complex ability ranged from 26.85 to 80.63 mL, and protein content showed a high correlation with SDS-sedimentation in the germplasms. Verify the result of the enzymatic method of arabinoxylan, the reliability of the experimental method was determined through repeatability, reproducibility, and recovery. The average value of the 614 resources was 51.64 mg/g of whole grain, and when classified according to the country of origin, the South Korean origin resources tended to have a higher content compared to the genetic resources of other countries. These results are expected to be used as basic data for setting standards for whole grain quality in wheat breeding systems.